Pragmatic Properties Of Lexical Units In Lyrical Discourse - Nurimova Diyora Qurbonovna (Zien Journals, 2025)
This article describes the concept of lexical unit and its essence. The use of lexical units in lyrical texts and the pragmatic feaures they represent are theoretically described. Pragmatic features of lexical units in Usman Azim’s works are analyzed.
Keywords: language; discourse; pragmatics